Associations Between Genotype and Peripheral Complement Proteins in First-Episode Psychosis: Evidences From C3 and C4 - Chen, Yu; Zhao, Zhenguo; Lin, Fen; Wang, Lifang; Lin, Zheng; Yue, Weihua (Frontiers in Genetics, 2021)
Schizophrenia is a common neuropsychiatric disorder with complex pathophysiology. Recent reports have suggested that complement system alterations contribute to pathological synapse elimination, which were associated with psychiatric symptoms in schizophrenia. Complement component 3 (C3) and complement component 4 (C4) may play a central role in the complement cascade whose activation is indispensable for all the vital functions performed by this system. In the present study, we compared C3 and C4 protein levels in first-episode schizophrenic patients and those in healthy controls. Then we explored whether single nucleotide polymorphisms (SNPs) at C3 or C4 genes was an important determinant of blood levels of C3 or C4 protein. In total, 181 first episode schizophrenia patients and 204 healthy control subjects were recruited after providing written informed consent. Serum C3 and C4 protein levels were measured by using the turbidimetric inhibition immunoassay. The C3 or C4 polymorphisms were genotyped by using the MassArray Sequenom genotyping. Our results suggested that three SNPs were associated with susceptibility of schizophrenia (rs11569562: A>G, p = 0.048; rs2277983: A>G, p = 0.040; rs149898426: G>A, p = 0.012). However, no haplotype was found to be significantly associated with risk of schizophrenia. The first-episode schizophrenic patients showed elevated serum levels of C3 (p = 4.3E-07) and C4 (p = 2.1E-05) than healthy control subjects. The patients carrying AG genotype of rs149898426 in C4 showed significantly higher C4 levels than those carrying GG genotypes (p = 0.0166). Overall, our findings indicated an alteration of the complement system in FEPs, which were likely due to the genetic factors, especially C4. Further studies with larger sample sizes needs to be validated the results of the present study.